Hospital Ownership and Minimum Service Standards Achievement: Empirical Evidence from Indonesia - Helsy Desvitasari (Journal of Health Service Administration and Hospital Management, 2025)
Healthcare service quality is a global priority, and in Indonesia it is assessed through the implementation of Minimum Service Standards (MSS) integrated with National Quality Indicators (NQI). MSS function as a standardized benchmark to evaluate hospital performance across different ownership types. This study aims to examine differences in MSS achievement between government and private hospitals. A quantitative comparative design was employed using secondary MSS/NQI data from 60 Type B and C general hospitals located in Java and Sumatra during 2023–2024. Hospitals were equally categorized by ownership (government and private). Data analysis included descriptive statistics, assumption testing, and independent sample t-tests to identify differences in composite MSS achievement between the two groups. The analysis demonstrated a statistically significant difference in MSS achievement based on hospital ownership. Private hospitals showed higher overall MSS attainment compared to government hospitals, with mean achievement scores of 94.05% and 87.21%, respectively (p < 0.001). This result indicates a measurable performance gap in meeting minimum service quality standards between ownership types. Hospital ownership is significantly associated with the achievement of Minimum Service Standards in Indonesia. Private hospitals consistently achieve higher MSS scores than government hospitals, suggesting structural differences in service quality performance. These findings provide empirical evidence on the role of ownership in hospital quality outcomes and highlight the importance of further investigation into organizational and management factors influencing MSS compliance.